THE TOURISM IN CROATIA: POLITICS, PROJECTS AND ENVIRONMENTAL SUSTAINABILITY - Ornella Albolino (Bollettino della Società Geografica Italiana)
The paper aims to consider the development and evolution of the tourism in Croatia and its economic and social impact. Croatia can be considered an interesting case study dealing with the relationship between tourism and sustainable development. In particular a special focus on local specificities seems to be present in policy planning and project implementation. Even if seaside tourism is prevailing, initiatives towards sustainability are concentrated on environmental, rural and cultural tourism. The Country is characterized by wide variety and rich cultural heritage and tourism development is one of the most Croatian important economic activity. Now there are many institutional documents for a sustainable tourism development but those plans are not followed by appropriate implementation instruments. Actually a coordinated and integrated sustainable tourism planning at national scale is absent. At local level, counties and Tourist offices show instead great attention to sustainability, creating projects for the development of rural and insular tourism. A particular example is the County of Istria: it is not characterized by seasonal tourism and it is able to promote an integrated tourism development.